Alteración emocional por enfermedad de cónyuge y su incidencia en la salud mental de un paciente de 62años de edad del cantón el Carmen - Loor Alcivar, Julady Jacqueline (2021)
Emotions appear in reaction to different situations due to environmental stimuli, they are intense and short-term responses, an emotional alteration is any state that generates significant discomfort in the person of long duration causing an affectation in the mood generating symptoms, such as sadness, euphoria, low tolerance for frustration, inconstancy, discouragement etc. Likewise, it affects the mental health of the individual, since this interferes in the way of acting, feeling, thinking and facing daily situations in a resilient way. Among the factors that harm mental health are the biological, psychological and social, each of these areas play a very important role in the development of some psychopathology with emotional alterations such as depression and anxiety. Some of the treatments that exist to treat these alterations according to their severity are medications, psychotherapy or in some cases a combination of both.